Smells like anthelmintic resistance—gastrointestinal prevalence, burden and diversity in dogs from Portugal - Batista, Cláudia Luís (2024)
Anthelmintic resistance has been documented worldwide, but few cases have been reported in dogs. Shelter dogs are a great opportunity to study intestinal helminths and assess their potential resistance to anthelmintic compounds. With these two goals in mind, 361 faecal samples were collected from dogs in 18 municipalities in Portugal, from 19 shelters and 11 private tutors. These samples were analysed using the Mini-FLOTAC before and 13 days after deworming. The percentage of faecal egg count reduction was calculated. Parasitic forms were identified in 22.4% of the samples collected: Trichuris vulpis (10.5%), Toxocara canis (8.0%), members of the family Ancylostomatidae (6.4%), Toxascaris leonina (0.8%), Dipylidium caninum (0.6%) and members of the family Taeniidae (0.3%). The first three nematode parasites showed the highest intensity of infection (2900, 1325, and 1265 eggs per gram, respectively). In the second faecal collection, parasites were present in 20.8% of the samples. The anthelmintics febendazole + pyrantel embonate + praziquantel and praziquantel + fenbendazole were ineffective for T. vulpis and members of the family Ancylostomatidae in 16.2% and 6.9% of the samples, respectively. The parasites identified are all potentially zoonotic. This study is the first to suggest a potential resistance of T. vulpis to anthelmintics.